Multimedia Learning Strategy (Animated Video) for Children With Slow Learner: English - Fitriani, Yuni; Sadiyyah, Enung Siti; Maryanti, Rina; Susetyo, Budi (Angstrom Centre of Education, 2024)
This study explores and applies multimedia learning strategies in the form of animated videos to overcome counting difficulties for students in class III-A at SDN Kemirimuka 2, Depok, by taking a research subject with the initials TZ. Numeracy difficulties can be a significant obstacle in learning mathematics, especially for students with slow learning characteristics such as TZ. This research aims to present an innovative and engaging solution through the application of multimedia learning media. The research began by specifically identifying the numeracy difficulties faced by TZ and designing a multimedia learning strategy that could adapt to the needs and characteristics of these students. The selection of animated video as learning media was based on its ability to present mathematical concepts in a visual and interesting way, suitable for the cognitive development level of grade III students. The research was conducted at SDN Kemirimuka 2, involving active participation from TZ, as well as monitoring her learning progress. The results showed that the multimedia learning strategy, specific to the use of animated videos, had a positive impact on TZ's understanding of math concepts and learning motivation. These findings can be used as a basis for further development of learning strategies that can be adopted for students with learning disabilities. Practical implications and recommendations for further development are discussed in this journal, making an important contribution to improving the mathematics learning of students with learning difficulties at the primary level.